How do you find the integral of #sin^2(x)cos^4(x) #?

Answer 1

#int sin^2(x)cos^4(x) dx#

#= -1/6 sin^5(x) cos(x)+7/24 sin^3(x) cos(x)-1/16 sin(x) cos(x)+1/16 x + C#

First note that:

#sin^2(x)cos^4(x) = (1 - cos^2(x)) cos^4(x) = -cos^(6)x + cos^4(x)#
#d/(dx) sin^5(x) cos(x) = 5 sin^4(x) cos^2(x) - sin^6(x)#
#color(white)(d/(dx) sin^5(x) cos(x)) = sin^4(x)(5 cos^2(x) - sin^2(x))#
#color(white)(d/(dx) sin^5(x) cos(x)) = (1-cos^2(x))(1-cos^2(x))(5 cos^2(x) - (1-cos^2(x)))#
#color(white)(d/(dx) sin^5(x) cos(x)) = (cos^4(x)-2cos^2(x)+1)(6 cos^2(x) - 1)#
#color(white)(d/(dx) sin^5(x) cos(x)) = 6cos^6(x)-13cos^4(x)+8cos^2(x)-1#
#d/(dx) sin^3(x) cos(x) = 3 sin^2(x) cos^(2)(x) - sin^4(x)#
#color(white)(d/(dx) sin^3(x) cos(x)) = sin^2(x)(3 cos^2(x) - sin^2(x))#
#color(white)(d/(dx) sin^3(x) cos(x)) = (1-cos^2(x))(3 cos^2(x) - (1-cos^2(x)))#
#color(white)(d/(dx) sin^3(x) cos(x)) = (-cos^2(x)+1)(4 cos^2(x) - 1)#
#color(white)(d/(dx) sin^3(x) cos(x)) = -4cos^4(x)+5cos^2(x)-1#
#d/(dx) sin(x) cos(x) = cos^2(x)-sin^2(x) = 2cos^2(x) - 1#
Now we can choose multipliers to make the running sum match each coefficient of #cos^(2k)(x)# in descending order:
#d/(dx) (-1/6 sin^5(x) cos(x)) = -cos^6(x)+13/6 cos^4(x)-4/3 cos^2(x)+1/6#
#d/(dx) (7/24 sin^3(x) cos(x)) = -7/6 cos^4(x)+35/24 cos^2(x) - 7/24#
#d/(dx) (-1/16 sin(x) cos(x)) = -1/8 cos^2(x) + 1/16#
#d/(dx) (1/16 x) = 1/16#
summing to: #-cos^6(x)+cos^4(x) = sin^2(x)cos^4(x)#

So:

#int sin^2(x)cos^4(x) dx#
#= -1/6 sin^5(x) cos(x)+7/24 sin^3(x) cos(x)-1/16 sin(x) cos(x)+1/16 x + C#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the integral of sin^2(x)cos^4(x), you can use trigonometric identities to simplify the expression. Start by using the identity sin^2(x) = 1 - cos^2(x), then apply the power-reducing formula cos^2(x) = (1 + cos(2x))/2. After simplifying, you'll have an expression that can be integrated more easily using basic integration techniques.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7